Accessibility to Transylvania´s cultural heritage through BIM-Heritage and community involvement - Chițonu, G C; Rolfsen, C N; Deaconu, O (IOP Publishing, 2020)
The rural areas of Transylvania offer important resources for developing research in diversity of the cultural heritage. Many of these communities have seen great changes in demographics over the last 30-50 years, and important cultural heritage from previous generations is being lost in lack of understanding, human resources and willingness to preserve the value of our joint cultural heritage. The research seeks a digitisation approach to preserving and promoting the local cultural heritage, as well as a social science approach, which seeks to find answers to how one can be able to preserve, maintain and promote this cultural heritage, something which, according to the study hypothesis, can only be done if the communities see the benefits of doing so. The digital shift has the ability to create another level of understanding, opening a vast horizon for accessibility and progress linked with BIM technology. As an answer to dealing with the climate changes, degradation of the buildings due to natural disasters or more from the indifference of the young generations in regard of history inheritance, the study could be a valuable instrument in enhancing BIM-Heritage methodologies.